Experiences of private sector quality care amongst mothers, newborns, and children in low- and middle-income countries: a systematic review - Joe Strong; Samantha R. Lattof; Blerta Maliqi; Nuhu Yaqub (BMC, 2021)
Abstract Background Experience of care is a pillar of quality care; positive experiences are essential during health care encounters and integral to quality health service delivery. Yet, we lack synthesised knowledge of how private sector delivery of quality care affects experiences of care amongst mothers, newborns, and children. To fill this gap, we conducted a systematic review that examined quantitative, qualitative, and mixed-methods studies on the provision of maternal, newborn, and child health (MNCH) care by private providers in low- and middle-income countries (LMICs). This manuscript focuses on experience of care, including respectful care, and satisfaction with care. Methods Our protocol followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Searches were conducted in eight electronic databases (Cumulative Index to Nursing and Allied Health, EconLit, Excerpta Medica Database, International Bibliography of the Social Sciences, Popline, PubMed, ScienceDirect, and Web of Science) and two websites and supplemented with hand-searches and expert recommendations. For inclusion, studies examining private sector delivery of quality care amongst mothers, newborns, and children in LMICs must have examined maternal, newborn, and/or child morbidity or mortality; quality of care; experience of care; and/or service utilisation. Data were extracted for descriptive statistics and thematic analysis. Results Of the 139 studies included, 45 studies reported data on experience of care. Most studies reporting experience of care were conducted in India, Bangladesh, and Uganda. Experiences of private care amongst mothers, newborns, and children aligned with four components of quality of care: patient-centeredness, timeliness, effectiveness, and equity. Interpersonal relationships with health care workers were essential to experience of care, in particular staff friendliness, positive attitudes, and time spent with health care providers. Experience of care can be a stronger determining factor in MNCH-related decision-making than the quality of services provided. Conclusion Positive experiences of care in private facilities can be linked more broadly to privileges of private care that allow for shorter waiting times and more provider time spent with mothers, newborns, and children. Little is known about experiences of private sector care amongst children. Trial registration This systematic review was registered with the PROSPERO international prospective register of systematic reviews (registration number CRD42019143383 ).